2018
DOI: 10.25165/j.ijabe.20181102.3157
|View full text |Cite
|
Sign up to set email alerts
|

Droplet deposition and efficiency of fungicides sprayed with small UAV against wheat powdery mildew

Abstract: Small unmanned aerial vehicle (UAV), a timely and effective pesticide sprayer, can be used to spray pesticide in a high efficiency without harming the crop, and is especially suitable for spraying for small farms and hills in Asian countries. In recent years, it has been chosen as a key and new technique for pesticide application. This paper studied the impact of UAV (UAV N-3) spraying parameters (different working height and different spraying concentrations) on the deposition of droplets on the wheat canopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 5 publications
1
55
0
Order By: Relevance
“…For instance, Zhang et al started to focus on UAV application for citrus and found the variation of droplet distribution [12] , while Tang et al concentrated on the deposition changes affected by tree shapes [13] . Similar studies regarding UAVs and spray factors include T10 UAV for wheat scab control [14] , Response Surface Method for the test of P20 UAV parameters [15] , tree shapes and flight heights for the deposition of 3W-LWS-Q60S [16] , the comparison of four types of UAVs [17] , the method of detection of effective spray swath of 3WQF120-12 [18] , different operation parameters for several stages of corns [19] , low-attitude droplets deposition [20] , drift caused by different types of UAVs [21] , deposition on pineapple trees impacted by operation parameters [22] and the control effect of wheat powdery mildew using different operation parameters [23] . Until 2019, this kind of study is still heated discussed [24][25][26] .…”
Section: Key Technology Of Caused Results Of Uav Downwash Acting On Smentioning
confidence: 99%
“…For instance, Zhang et al started to focus on UAV application for citrus and found the variation of droplet distribution [12] , while Tang et al concentrated on the deposition changes affected by tree shapes [13] . Similar studies regarding UAVs and spray factors include T10 UAV for wheat scab control [14] , Response Surface Method for the test of P20 UAV parameters [15] , tree shapes and flight heights for the deposition of 3W-LWS-Q60S [16] , the comparison of four types of UAVs [17] , the method of detection of effective spray swath of 3WQF120-12 [18] , different operation parameters for several stages of corns [19] , low-attitude droplets deposition [20] , drift caused by different types of UAVs [21] , deposition on pineapple trees impacted by operation parameters [22] and the control effect of wheat powdery mildew using different operation parameters [23] . Until 2019, this kind of study is still heated discussed [24][25][26] .…”
Section: Key Technology Of Caused Results Of Uav Downwash Acting On Smentioning
confidence: 99%
“…First, the carrier volume of the UAV‐IS (151 L ha −1 ) was 20% lower and generated fewer droplets with a higher concentration of glufosinate compared to the 187 L ha −1 carrier volume of the broadcast system, likely favoring herbicide absorption by the plant . Second, and more likely, the downwash air generated by the propellers of the UAV‐sprayer favored more N. tobacco leaf movement, so leaves were exposed to the herbicide on both the adaxial and abaxial sides, effectively increasing the amount of herbicide reaching deeper into the canopy of the target plants . This latter situation was more likely to occur for N. tobacco , which has erect growth and long leaves, than for K. striata , which exhibits prostrate growth and very small leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Reference Fixed-wing [23][24][25][26] Single-rotor helicopter [27][28][29][30][31] Quad copter [32][33][34][35][36] Hexa copter [30,[37][38][39][40] Octo copter [41][42][43][44][45] (a) (b) (c) (d) (e) Current RPAs applications for precision agriculture are mainly developed for small-to mediumsized crops, using rotary-wing RPASs with small range and endurance operation, leaving aside largesized crops, but farmers with a lot of hectares of land find it difficult to reach each corner of field for inspection each time. The fixed-wing RPAS does this task without any hiccup, as farmers can do regular air monitoring of fields to know the status of their crops at regular intervals of time.…”
Section: Typementioning
confidence: 99%